2018
DOI: 10.14202/vetworld.2018.1237-1243
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of Ocimum sanctum Linn. ethanolic extract on human embryonic kidney-293 cells as in vitro model of neurodegenerative disease

Abstract: Aim:This study aimed to analyze the neuroprotective effect of Ocimum sanctum Linn. ethanolic extract (OSE) on human embryonic kidney-293 (HEK-293) cells as the in vitro model of neurodegenerative diseases.Materials and Methods:In this research, HEK-293 cells divided into five groups consisting of normal and healthy cells (NT), cells treated with Camptothecin 500 µM as the negative control, cells treated with trimethyltin 10 µM (TMT), cells treated with OSE 75 µg/ml, and cells pre-treated with OSE 75 µg/ml then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Cell viability was determined by MTT assay as previously describe [17] in the absence or presence of 50, 70, 100 or 200 ug/ml EEOS. After 48 h treatments, culture medium was aspirated and cells were incubated with MTT (0,5 mg/ml) at 37 °C for 4 h. The viable cell number was directly proportional to the production of formazan, which was dissolved in isopropanol and determined by measuring the absorbance at 570 nm using a microplate reader (SpectraMAX 360 pc, Molecular Devices, Sunnyvale, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability was determined by MTT assay as previously describe [17] in the absence or presence of 50, 70, 100 or 200 ug/ml EEOS. After 48 h treatments, culture medium was aspirated and cells were incubated with MTT (0,5 mg/ml) at 37 °C for 4 h. The viable cell number was directly proportional to the production of formazan, which was dissolved in isopropanol and determined by measuring the absorbance at 570 nm using a microplate reader (SpectraMAX 360 pc, Molecular Devices, Sunnyvale, CA).…”
Section: Methodsmentioning
confidence: 99%
“…In Indonesia, Ocimum sanctum is very easy to find and use commonly as vegetable food. It is well-known that Ocimum sanctum acts as a chemopreventive, anti-carcinogenic, free radical scavenger and also used as a medication for neurodegenerative diseases [15, 16, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…In-vitro studies also revealed the ability of the said combination to increase cell viability of PTZ-treated HEK-293 cells by 267%. Various studies in the literature have refuted the relationship of cell viability with neuroprotective efficacy [ 92 , 93 , 94 ]. HEK 293 cells were initially derived in 1973 from a kidney [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cells also express endogenous voltage-activated ion currents similar to neurons [ 97 ]. Therefore, HEK293 cells can be used to mimic neurodegenerative diseases [ 93 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…radioprotective [7,8] , anticarcinogenic [7] , antioxidant [7,9] , anticandidal [10] , antileishmanial, immunomodulatory [11] , immunotherapeutic [12] , antimicrobial [9,13] , antifertility [14] , anti-inflammatory [15] and neuroprotective [16] properties of this plant have also been reported. The main constituent of the essential oil of O. sanctum from different regions of the world is represented in Table 1 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] .…”
mentioning
confidence: 99%